The potential therapeutic value and application prospect of engineered exosomes in human diseases - Liu, Gege; Wu, Junlu; Chen, Guofei; Shang, Anquan (Frontiers in Cell and Developmental Biology, 2022)
Exosomes are tiny vesicles produced by a wide range of cells that contain complex RNA and protein. In the diagnosis, treatment, and prevention of illness, they offer great potential. In vitro engineering technique modifies exosomes to produce designed exosomes that include nucleic acids, proteins, and medicines, and are targeted to particular tissues or cells. Their applications range from tumor imaging and gene therapy to vaccine production and regenerative medicine to targeted medication delivery. Many disciplines have promising futures for using this technology. In this review, we’ll look at the potential therapeutic usefulness and use of engineered exosomes in a variety of human illnesses with various systemic manifestations.